Consentability : consent and its limits / by Nancy S. Kim. - Kim, Nancy S., 1966- (Cambridge University Press, 2019)
Problems regarding the nature of consent are at the heart of many of today's most pressing issues. For example, the #MeToo movement has underscored the need to move beyond viewing consent as a simple matter of yes or no. Consent is complex because humans and their relationships are complicated. Humans, as a result of cognitive limitations and emotional and physical vulnerabilities, are susceptible to manipulation and mistakes. Given the potential for regret, are there some things to which one should not be permitted to consent? The consentability quandary becomes more urgent with technological advances. Should we allow body hacking? Cryogenics? Consumer travel to Mars? Assisted suicide? In Consentability: Consent and Its Limits, Nancy S. Kim proposes a bold, original framework for evaluating consentability, which considers the complexities surrounding consent.